Sciences for the IB MYP 1 : MYP by Concept 1 - Paul Morris; Patricia Deo (London, United Kingdom Hodder Education, 2016)
Exam Board: IBLevel: MYPSubject: ScienceFirst Teaching: September 2016First Exam: June 2017Develop your skills to become an inquiring learner; ensure you navigate the MYP framework with confidence using a concept-driven and assessment-focused approach to Sciences presented in global contexts.- Develop conceptual understanding with key MYP concepts and related concepts at the heart of each chapter.- Learn by asking questions with a statement of inquiry in each chapter. - Prepare for every aspect of assessment using support and tasks designed by experienced educators.- Understand how to extend your learning through research projects and interdisciplinary opportunities.
Keywords: MYP-Sciences + PYP Office -- MYP-Sciences + PYP Office